Cengkerik Trading - J Mianus, Adelheid; Zurnosh, Hafizah; Udin, Haslinda; Kudil, Nor Hadayu; Abdul Karim, Mohd Mizanuza'im (2013)
Cengkerik Trading is a home-grown crickets business which rarely found in our country. We see potential in this business field. Our business will help those end users out there who need crickets in their daily activity. Our main business purpose is to be the mass supplier of crickets to numerous customers. The nature of our business is in-house breeding of crickets and later on, supplies them to customers. The business is located in Kg. Dombiku Kepayan. The land is 1 acre area concentrates on the office function and nursery where all the crickets will be kept. We chooses to breed crickets and being a mass supplier due to its bright future business potential and future increasing demand here in Sabah. This business is focusing in breeding house crickets and field crickets. Crickets usually used as food for fish and for fishing activities. There are about 900 species of crickets. Crickets are proven to be harmless to humans. Besides that, there are other positive impacts of crickets on the ecosystem such as renewing soil minerals. Crickets are also an important source of food to other animals.